Three Subband Occupation of the Two‐Dimensional Electron Gas in Ultrathin Barrier AlN/GaN Heterostructures. (9th September 2020) - Yang, Liuyun; Wang, Xinqiang; Wang, Tao; Wang, Jingyue; Zhang, Wenjie; Quach, Patrick; Wang, Ping; Liu, Fang; Li, Duo; Chen, Ling; Liu, Shangfeng; Wei, Jiaqi; et al.
Abstract: Ultrathin barrier AlN/GaN heterostructure with record low sheet resistance of 82 Ω sq −1 is achieved by molecular beam epitaxy, where Shubnikov‐de Haas oscillations (SdHOs) and quantum Hall effect (QHE) of two‐dimensional electron gas (2DEG) are observed. The fast Fourier transform analysis of the SdHOs demonstrates a three‐subband occupation in the triangle quantum well for the first time, with the electron density of n 1 = 2.2 × 10 13  cm −2, n 2 =  2.3 × 10 12 cm −2, and n 3 = 8.8 × 10 11 cm −2, respectively, and the corresponding energy of 265, 28, and 11 meV below Fermi level. The three‐subband QHE with a superposed feature is also demonstrated for the first time in AlN/GaN heterostructure, with large filling factors at high electron densities. By analyzing the first subband as the dominant part of the superposed QHE, the transport physics of a special magneto‐intersubband scattering is revealed. These results contribute to a better understanding of the quantum physics for 2DEG, leading to a versatile functionality for AlN/GaN devices. Abstract : Three‐subband occupation of 2D electron gas has been experimentally observed in an ultrathin barrier AlN/GaN heterostructure with very low sheet resistance via Shubnikov‐de Haas oscillations. Transport parameters of the three subbands including energy level, electron density, and quantum scattering time are figured out. The quantum Hall effect of the multi‐subband system is also analyzed.